CIPP Model Evaluation on TOEFL Course at Higher Education - Eva Nur Mazidah; Lailatul Masruroh (Prodi Pendidikan Bahasa Inggris, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Islam Darul Ulum Lamongan*, 2024)
To assist future graduates, students of the English Language Education Study Program receive specialized training in a 'TOEFL' course that is specifically designed to prepare them for the TOEFL test. The objective of this research is to assess the effectiveness of the TOEFL course offered in this study program as a mandatory advanced course, which can be taken in either the sixth or eighth semester. This study presents a CIPP (Context, Input, Process, Product) evaluation methodology specifically designed to meet the requirements and unique features of the TOEFL course at Universitas Qomaruddin. This research is needed to investigate (1) What are the outcomes of evaluating TOEFL courses using the CIPP approach? (2) What are the key enhancements that need to be implemented in order to maximize the program's beneficial influence, as perceived by students and lecturers, in terms of program outcomes? By employing this quantitative and qualitative methodologies, our aim is to provide a comprehensive assessment framework capable of addressing several research inquiries. The research involved a total of 42 students, a lecturer, and a head of the study program. The research data utilized encompass surveys, interviews, and documentation. The quantitative data were analyzed using descriptive statistics, while qualitative data from interviews and documentation were examined thematically to complement and explain the numerical findings. ubsequently, the data is scrutinized and inferences are made. The results show TOEFL course was generally executed well proven by effectiveness from context evaluation (82%), input evaluation (83%), process evaluation (86%), and product evaluation (82%). These findings indicate that the TOEFL course meets its objectives effectively. However, continuous improvements in infrastructure, resources, and engagement strategies are recommended to enhance the program's overall quality and long-term impact. This study provides practical insights for curriculum designers and educators seeking to evaluate and optimize similar programs.